Paradoxes of pandemic infection control: Proximity, pace and care within and beyond SARS-CoV-2 - Leah Williams Veazey; Alex Broom; Katherine Kenny; Chris Degeling; Mary Wyer; Suyin Hor; Jennifer Broom; Penny Burns; Gwendolyn L. Gilbert (Elsevier, 2022)
From the adoption of mask-wearing in public settings to the omnipresence of hand-sanitising, the SARS-CoV-2 pandemic has brought unprecedented cultural attention to infection prevention and control (IPC) in everyday life. At the same time, the pandemic threat has enlivened and unsettled hospital IPC processes, fracturing confidence, demanding new forms of evidence, and ultimately involving a rapid reassembling of what constitutes safe care. Here, drawing on semi-structured interviews with 63 frontline healthcare workers from two states in Australia, interviewed between September 2020 and March 2021, we illuminate some of the affective dimensions of IPC at a time of rapid change and evolving uncertainty. We track how a collective sense of risk and safety is relationally produced, redefining attitudes and practices around infective risk, and transforming accepted paradigms of care and self-protection. Drawing on Puig de la Bellacasa's formulation, we propose the notion of IPC as a multidimensional matter of care. Highlighting the complex negotiation of space and time in relation to infection control and care illustrates a series of paradoxes, the understanding of which helps illuminate not only how IPC works, in practice, but also what it means to those working on the frontline of the pandemic.